2021
DOI: 10.1016/j.hpb.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of factors which reduce the length of stay associated with elective laparoscopic cholecystectomy

Abstract: Background Laparoscopic cholecystectomy is a safe ambulatory procedure in appropriately selected patients; however, day case rates remain low. The objective of this systematic review and meta-analysis was to identify interventions which are effective in reducing the length of stay (LOS) or improving the day case rate for elective laparoscopic cholecystectomy. Methods Comparative English-language studies describing perioperative interventions applicable to elective lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 108 publications
0
6
0
2
Order By: Relevance
“…Thus, about 30% of patients undergoing surgical intervention present with PONV, which although these symptoms are to be expected continues to be a reason for lengthening hospital stays and, more importantly, discomfort in patients [4, 5]. The incidence of postoperative pain is reported to be 46–72% [6], and this level persists despite recent advances in understanding its pathophysiology, the advent of analgesics and potent antiemetics, as well as technical refinements in the LC procedure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, about 30% of patients undergoing surgical intervention present with PONV, which although these symptoms are to be expected continues to be a reason for lengthening hospital stays and, more importantly, discomfort in patients [4, 5]. The incidence of postoperative pain is reported to be 46–72% [6], and this level persists despite recent advances in understanding its pathophysiology, the advent of analgesics and potent antiemetics, as well as technical refinements in the LC procedure [7].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the median LOS reported ranged between 2 days and 2.2 days [ 13 24 ]. Moreover, a recent meta-analysis that included 10,615 patients found that the mean LOS was 61.2 hours [ 25 ]. However, given that the hospitals enrolled in this meta-analysis were diverse and that the LOS can be affected by financial or organizational factors, differences may occur depending on hospital size and insurance coverage between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from clinical studies of the effect of pneumoperitoneal pressure reduction no difference observed in the average life expectancy of patients who underwent surgery with pressure ≤ 10 mm Hg and patients who were treated with a pressure of 10-15 mm Hg [24].…”
Section: Technical Aspects Of Laparoscopic Cholecystectomymentioning
confidence: 99%